2021
DOI: 10.1109/tcst.2019.2959535
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Regulation in Buck–Boost Converters Feeding an Unknown Constant Power Load: An Adaptive Passivity-Based Control

Abstract: Rapid developments in power distribution systems and renewable energy have widened the applications of dcdc buck-boost converters in dc voltage regulation. Applications include vehicular power systems, renewable energy sources that generate power at a low voltage, and dc microgrids. It is noted that the cascade-connection of converters in these applications may cause instability due to the fact that converters acting as loads have a constant power load (CPL) behavior. In this paper, the output voltage regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
(43 reference statements)
0
34
0
Order By: Relevance
“…The elements of x * are selected to achieve the control objectives and fixed by a secondary level controller. The reference of the DC-link voltage is selected as v * dc = V * dc (constant), i * Bat comes from (29), and i * PV is obtained from a maximum power point tracker (MPPT) algorithm such as an incremental conductance (IC) algorithm [9,34].…”
Section: Ida-pbc Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The elements of x * are selected to achieve the control objectives and fixed by a secondary level controller. The reference of the DC-link voltage is selected as v * dc = V * dc (constant), i * Bat comes from (29), and i * PV is obtained from a maximum power point tracker (MPPT) algorithm such as an incremental conductance (IC) algorithm [9,34].…”
Section: Ida-pbc Controlmentioning
confidence: 99%
“…In order to implement the proposed controller, voltages and currents in the system must be measured. In addition, the calculation of the battery current reference, (29), requires knowledge of the power value of the CPL, P CPL .…”
Section: Load Power Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results revealed that the proposed PID-based fuzzy logic controller reduced an integral square error as well as the overshoot value. The voltage regulation of a buck-boost converter was proposed by Soriano-Rangel et al (2020) that utilize an adaptive passivity-based control in the power distributed systems. This approach employs the cascaded converter connection to construct a feedback controller.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…A passivity-based control was suggested in [ 13 ] to stabilize voltage fed to a microgrid. The proposed strategy achieved Lyapunov asymptotic stability through a state-feedback control law, which required an online invariance and immersion power estimator.…”
Section: Introductionmentioning
confidence: 99%